Restoration ecology - Greipsson, Sigurdur (Jones and Bartlett Publishers, 2011)
The Earth's biodiversity is at risk, as delicate ecosystems struggle to overcome global climate change, rain forest destruction acid rain overfishing, erosion, and a host of other interconnected environmental problems. Written for upper-level undergraduate and graduate students, Restoration Ecology addresses these growing environmental Concerns and offers practical and economical solution. The text opens with a look at fundamental ecological principles critical to understanding restoration, including nutriert cycing and factors that regulate ecosystem function, and continues on to explore restoration in practice, providing real-life accounts of the restoration of various disturbed ecosystems. The final section delves into the planning implementation monitoring, and appraisal of restoration work. -- Book Jacket